2017
DOI: 10.1111/ijsa.12181
|View full text |Cite
|
Sign up to set email alerts
|

Fearless dominance and performance in field sales: A predictive study

Abstract: In a prospective study of 150 junior salespeople in the same company, we examined the relation between fearless dominance, which is a dimension of trait psychopathy, and objective performance in field sales. After controlling for demographic variables, length of job tenure, initial sales training quality, and disciplined achievement motivation, the results supported an inverted U‐shaped relation, which showed that, after a certain turning point, increases in fearless dominance resulted in decreases in performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…Similar examples of the above are found in studies by: Locander et al (2014), Arndt and Wang (2014), Manna and Smith (2004), Titze et al (2017), Fu et al (2017 and Mullins et al (2015).…”
Section: 25supporting
confidence: 85%
“…Similar examples of the above are found in studies by: Locander et al (2014), Arndt and Wang (2014), Manna and Smith (2004), Titze et al (2017), Fu et al (2017 and Mullins et al (2015).…”
Section: 25supporting
confidence: 85%
“…Prior organizational research has supported this account, with studies documenting curvilinear effects for narcissism and leadership effectiveness (Grijalva et al, 2015), psychopathy and commission sales performance (Titze, Blickle, & Wihler, 2017), and dark personality traits in general and leadership performance (Benson & Campbell, 2007). Grijalva and colleagues (2015) accounted for this using behavioral threshold theory, which suggests that different levels (or subfacets) of a trait may have different, or even opposite, relationships with particular outcomes of interest.…”
Section: Curvilinear Associationsmentioning
confidence: 99%
“…Boldness-related traits may be relevant to interpersonal manipulativeness if such traits make psychopathic individuals more persuasive, allowing such individuals to penetrate deeper into social networks before their more clearly aversive traits (i.e., antagonism, disinhibition) are detected. One study found that boldness exhibited a curvilinear relation with sales performance, such that increases in boldness until –.39 standard deviations were associated with increased sales performance, after which point, boldness was associated with decreased performance (Titze, Blickle, & Wihler, 2017). Although there is little research available on the relation of boldness and persuasiveness per se, there is some research available, particularly within the industrial-organizational psychology literature, linking the main personality correlates of boldness—extraversion and (low) neuroticism (Miller & Lynam, 2012).…”
Section: Boldness and Persuasivenessmentioning
confidence: 99%